Ethnomathematics: Mathematical Exploration on Batik Gedog Tuban - Ervinawati, Yulia (Universitas Negeri Surabaya, 2019)
Batik Gedog Tuban has been one of prominent Batik types in Tuban. This batik has a variety of patterns with diverse colors. This study aimed to analyze the mathematical value within Batik Gedog Tuban. This study used a qualitative descriptive with an ethnographic approach. Data were collected by the study of literature, observation, interview, note, and documentation. The results showed that there were several mathematical concepts contained in Batik Gedog Tuban such as geometry concepts, geometry transformation, and congruence